Molecular structure and computational studies on 2-((2-(4-(3-(2,5-dimethylphenyl)-3-methylcyclobutyl)thiazol-2-yl)hydrazono)methyl) phenol monomer and dimer by DFT calculations - Karakurt, Tuncay; Cukurovali, Alaaddin; Subasi, Nuriye Tuna; Kani, Ibrahim (Elsevier Science Bv, 2016)
The title compound, 2-((2-(4-(3-(2,5-Dimethylphenyl)-3-methylcyclobutyl)thiazol-2-yl)hydrazono) methyl)phenol, was characterized by single-crystal X-ray diffraction. In order to calculate molecular geometry along with the infrared, Atoms in Molecules (AIM) analysis and H-1 and C-13 NMR chemical shift values, the density functional theory (DFT) method with 6-311G++(d,p) basis set was utilized. Experimental data were then used for comparison. While the title crystal structure is photochromic, the molecule is nonplanar. It takes on an enol form including a forceful intramolecular O-H center dot center dot center dot N hydrogen bond as well as a forceful intermolecular N-H center dot center dot center dot N hydrogen bond. The 6-311G++(d,p) basis function was used to examine the intramolecular tautomerism single proton transfer reaction of the hydrogen-bonded enol imine and keto amine monomer in the title crystal structure at the B3LYP theory level. Further, the frontier molecular orbitals (FMO), molecular docking and NLO properties were studied by using theoretical calculations. The calculated NLO properties of title compound are much greater than urea. The title compound generates a stable complex with CDK2 as is distinct from the binding energy values. These results proposed that the compound might exhibit inhibitory effect against CDK2. These are important in development of new antitumor agent. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: X-ray diffraction; IR and NMR spectroscopy; NLO; AIM; Antitumor agent